Cryogenic Photonic Readout Based on Thin-Film Lithium Niobate Mach–Zehnder Modulators - Hailong Han; Xiaoping Liu; Huazhan Liang; Lingyun Li; Hao Li; Lixing You (IEEE Photonics Journal)
Cryogenic data transfer has numerous applications at 4.2 K for extracting data from supercomputers and quantum computers to address interface bottlenecks. The external modulation of data transmission across temperature zones is achieved through the use of electro-optic modulators. The performance of a thin-film lithium niobate (TFLN) Mach-Zehnder modulator was examined at cryogenic temperatures. Low-frequency measurements indicate that the Vπ (voltage needed for π phase shift) of the modulator increases as the temperature decreases from 298 K to 4.2 K. A comparison was conducted between the readout performance of the electrical wire link and the optical fiber link, spanning from 4.2 K to 298 K. Additionally, high-speed data transmission was successfully demonstrated in a 4.2 K environment without the need for cryogenic electric amplifiers, achieving signals of up to 30 Gbps. The proposed solution holds potential benefits for both classical and quantum computers in alleviating interface bottlenecks.